Profitabilitas, Likuiditas, dan Leverage Terhadap Pengungkapan CSR Perusahaan - Heksa Noor Octaviandito (Journal of Management and Bussines (JOMB), 2023)
This study aims to test and analyze the effect of profitability, liquidity and leverage on the disclosure of Corporate Social Responsibility of Food and Beverages manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. This research method is quantitative. Data collection techniques using secondary data with purposive sampling method. Based on the criteria determined by the researcher, a sample of 17 companies was found with a total sample of 85 observations. The analysis technique uses multiple linear regression using the SPSS Version 26 tool. The results show that profitability does not affect the disclosure of Corporate Social Responsibility (CSR) disclosure of Corporate Social Responsibility (CSR) because the results of the profitability t test have a sig value of 0.834, so the sig value is obtained is greater than 0.05 or 5%; b) liquidity affects the disclosure of Corporate Social Responsibility (CSR) because the results of the t-test for liquidity have a value of 0.010, so the sig value obtained is less than 0.05 or 5%; c) leverage has no effect on disclosure of Corporate Social Responsibility (CSR) because the leverage t-test results have a sig value of 0.728, so the sig value obtained is greater than 0.05 or 5%. In conclusion, the liquidity ratio has an effect on the disclosure of Corporate Social Responsibility (CSR). Meanwhile, profitability and leverage ratios have no effect on the disclosure of Corporate Social Responsibility (CSR). Keywords: Corporate Social Responsibility (CSR), Leverage, Liquidity, Profitability